Analysis of Academies Society Awareness for The ‚Green Campus" Program in UPN ‚Veteran" East Java - Supriyono (Nusantara Science and Technology Proceedings)
Green campus program is a manifestation of a university that utilizing friendly environment energy into the real act of acknowledge environment issues. Therefore through this program will encourage awareness and careless from the university society itself to keep the environment clean, beside that university also a place to gather up young intellectuals as the next generation of the nation. This program could be role model or good example for other institution to keep sustainability of the environment clean. UPN Veteran East Java as a well-known university in Surabaya is really care to the environment‘s issues so therefore a green campus program. Due to that matter, this research is to know how far the social factor, learning and personally encourage academies society to apply green campus program in the UPN Veteran East Java college society. In this research, the researcher used 100 persons as the sample and the population which is all the active academies society in UPN Veteran of East Java. This research is a descriptive quantitative research by spreading questionnaire. Analysis technique for this research using SEM method based on component with data analysis PLS. The result for this research is to describe the awareness of academies society in contributing for the green campus program in UPN Veteran of East Java.